2021
DOI: 10.1039/d0qo01322f
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light induced divergent dearomatization of indole derivatives: controlled access to cyclobutane-fused polycycles and 2-substituted indolines

Abstract: A photocatalytic protocol for the divergent dearomative functionalization of indole derivatives is reported. Under the irradiation of visible-light, either dimerization or reduction occurs selectively by manipulating the reaction parameters, leading...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Because the T 1 state is accessed directly without having to generate S 1 , only stepwise ortho -and para -cycloadditions are observed. Examples of EnT-induced dearomative ortho -cycloadditions include reactions of indoles as reported by You, Oderinde, Fu, and Zhang . In addition, early work from Meggers demonstrated the dearomatization of benzofuran and benzothiophene .…”
Section: Introductionmentioning
confidence: 99%
“…Because the T 1 state is accessed directly without having to generate S 1 , only stepwise ortho -and para -cycloadditions are observed. Examples of EnT-induced dearomative ortho -cycloadditions include reactions of indoles as reported by You, Oderinde, Fu, and Zhang . In addition, early work from Meggers demonstrated the dearomatization of benzofuran and benzothiophene .…”
Section: Introductionmentioning
confidence: 99%
“…Later, the groups of Zhang and Oderinde independently reported the intermolecular dearomative [2+2] cycloaddition reactions of indole derivatives, using Ir-complexes as the photocatalysts via a pathway involving an energy transfer event (Scheme 65). 117,118 Contrast to the dimerization in Zhang's work, indolines were afforded when the reaction was conducted in the presence of DIPEA as an electron sacrificial reagent and hydrogen source. 117 In 2019, the Ko ¨nig group disclosed a Birch-type photoreduction of arenes and heteroarenes by sensitized electron transfer (Scheme 66).…”
Section: Energy Transfer (Et) To Arenesmentioning
confidence: 92%
“…117,118 Contrast to the dimerization in Zhang's work, indolines were afforded when the reaction was conducted in the presence of DIPEA as an electron sacrificial reagent and hydrogen source. 117 In 2019, the Ko ¨nig group disclosed a Birch-type photoreduction of arenes and heteroarenes by sensitized electron transfer (Scheme 66). 119 When investigating the effects of photocatalyst, it was observed that the photocatalyst Ir(ppy) 3 with a higher reduction potential was not be able to reduce anthracene, whereas another weaker reductant Ir[dF(CF 3 )ppy] 2 (dtbpy)PF 6 promoted the dearomatization reaction efficiently.…”
Section: Energy Transfer (Et) To Arenesmentioning
confidence: 92%
“…Protonation of int2 delivers the enol intermediate int3 . The reduced state of α-aminoradical III ( E ox = −1.12 V versus SCE) is strong enough to promote the direct SET reduction of int3 ( E ox = −0.8 V versus SCE) to afford radical anionic intermediate int4 20,21 and the formation of iminium ion IV is strongly supported by the direct observation of in situ generated acetaldehyde as shown in Scheme 4. Finally, int4 goes through the protonation to give the desired product 2c .…”
mentioning
confidence: 82%